2020
DOI: 10.1002/hep4.1584
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Liver X Receptor α Sensitizes Mice to T‐Cell Mediated Hepatitis

Abstract: Autoimmune hepatitis (AIH) is an inflammatory disease of the liver. Liver X receptors (LXRs), including the α and β isoforms, are previously known for their anti‐inflammatory activities. The goal of this study is to determine whether and how LXR plays a role in AIH. LXRα gain‐of‐function and loss‐of‐function mouse models were used, in conjunction with the concanavalin A (ConA) model of T‐cell mediated hepatitis. We first showed that the hepatic expression of LXRα was decreased in the ConA model of hepatitis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(57 reference statements)
2
6
0
Order By: Relevance
“…In line with our data, a recent study reported that consecutive activation of LXRα exacerbated ConA-induced hepatitis ( 45 ), which supported a pathogenic role of LXRα during AIH development. Additionally, LXRα −/− mice fed with a high-fat and high-cholesterol diet were resistant to ConA due to the dysfunction of invariant NKT cells ( 46 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our data, a recent study reported that consecutive activation of LXRα exacerbated ConA-induced hepatitis ( 45 ), which supported a pathogenic role of LXRα during AIH development. Additionally, LXRα −/− mice fed with a high-fat and high-cholesterol diet were resistant to ConA due to the dysfunction of invariant NKT cells ( 46 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our data, a recent study reported that consecutive activation of LXRa exacerbated ConA-induced hepatitis (45), which supported a pathogenic role of LXRa during AIH development. Additionally, LXRa −/− mice fed with a high-fat and high-cholesterol diet were resistant to ConA due to the dysfunction of invariant NKT cells (46).…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of iNKT cells in hepatic MNCs is decreased in LXRα-KO mice fed high-fat and high-cholesterol diet and the response to α-GalCer is impaired in these mice 18 . Con-A-induced hepatitis is attenuated in LXRα-KO mice and is exacerbated in constitutively active LXRα knock-in mice 33 . These findings indicate that LXRα and also LXRβ are involved in hepatic iNKT cell-mediated immune responses.…”
Section: Discussionmentioning
confidence: 96%